A atom-efficient cross-coupling reaction of aryl iodides with triarylbismuths catalyzed by immobilization of palladium(II)-Schiff base complex in MCM-41. Issue 17 (28th April 2016) - Xu, Caifeng; Yin, Lin; Huang, Bin; Liu, Haiyi; Cai, Mingzhong
Abstract: The first phosphine-free heterogeneous atom-efficient cross-coupling of aryl iodides with triarylbismuths was achieved in NMP using K2 CO3 as base at 110 °C in the presence of 2 mol % of an MCM-41-immobilized palladium(II)-Schiff base complex [MCM-41-N, N-Pd(OAc)2 ], yielding a variety of unsymmetrical biaryls in good to excellent yields. This new heterogeneous palladium catalyst exhibits high catalytic activity and can be recovered by a simple filtration of the reaction solution and recycled for at least 10 consecutive trials without any decreases in activity. Our system not only avoids the use of phosphine ligands, but also solves the basic problem of palladium catalyst recovery and reuse. Graphical abstract: